Pengaruh Game Online terhadap Perilaku Konsumtif: Studi Kasus Siswa MAN 1 dan MAN 2 Medan - M. Ikhwan Syarif; Raihan Adha Rahman Pohan; Dini Lestari (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The student research program investigates "The Influence of Online Games on Consumptive Behavior" among students of MAN 1 Medan and MAN 2 Medan. This study aims to answer two main problems: 1) determine the ratio of the impact of online game addiction on the consumptive behavior of students in the two schools, and 2) quantify the extent to which the impact of online game addiction has on their consumptive behavior. The research methodology involves using a questionnaire to collect data from respondents, and an Index Score (SI) is used to calculate the percentage of responses. Data analysis combines qualitative and quantitative approaches. The results of the study show that the impact of online game addiction on students' consumptive behavior in both schools is classified as "average" based on the score interpretation.